Learn Ncert All Solutions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Find and correct the errors in the statement: (3x + 2)^{2} = 3x^{2} + 6x + 4

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

Given,

(3x + 2)^{2} = 3x^{2} + 6x + 4

Solving LHS we get,

(3x + 2)^{2}

= (3x)^{2} + 2(3x)(2) + (2)^{2} [Using identity (a + b)^{2} = a^{2} + 2ab + b^{2}]

= 9x^{2} + 12x + 4

But RHS is given as 3x^{2} + 6x + 4

Thus, L.H .S. ≠ R.H.S.

The correct statement is (3x + 2)^{2} = 9x^{2 }+ 12x + 4

**☛ Check: **NCERT Solutions for Class 8 Maths Chapter 14

**Video Solution:**

## Find and correct the errors in the statement: (3x + 2)² = 3x² + 6x + 4

Class 8 Maths NCERT Solutions Chapter 14 Exercise 14.4 Question 9

**Summary:**

Find and correct the errors in the statement: (3x + 2)^{2} = 3x^{2} + 6x + 4. The correct statement is (3x + 2)^{2} = 9x^{2 }+ 12x + 4.

**☛ Related Questions:**

- Find and correct the errors in the following mathematical statement. Substituting x = -3 in (a) x2+ 5x + 4 gives (-3)2 + 5(-3) + 4 = 9 + 2 + 4 = 15 (b) x2 - 5x + 4 gives (-3)2 - 5(-3) + 4 = 9 - 15 + 4 = -2 (c) x2 + 5x gives (-3)2 + 5(-3) = -9 - 15 = -24
- Find and correct the errors in the statement: (y - 3)2 = y2 - 9
- Find and correct the errors in the statement: (z + 5)2 = z2 + 25
- Find and correct the errors in the statement: (2a + 3b)(a - b) = 2a2 - 3b2

Math worksheets and

visual curriculum

visual curriculum